Interactive Hybrid Book for Inclusive Reading Activities - Kevin Dwi Pradana; I G A Lokita Purnamika Utami; I Ketut Trika Adi Ana (Journal of Educational Study, 2026)
This study aims to develop an interactive hybrid book that integrates text, images, and sign language as a learning medium to facilitate English reading activities in inclusive classrooms. Specifically, the study seeks to identify the types of English reading materials needed by inclusive students, design an interactive hybrid book adapted to these needs, evaluate the validity of the content and media, and assess the practicality of the developed product. The study employed the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation phases. The research instruments included interview guides for needs analysis, interviews with teachers and students, a researcher’s journal, a product development progress sheet, expert judgment sheets for content and media validation, and practicality questionnaires. The results of the needs analysis revealed that inclusive students require visually engaging reading materials that incorporate multimodal elements, such as sign language, subtitles, and interactive features, to support their reading activities. The interactive hybrid book was designed in alignment with the Merdeka Curriculum and the principles of differentiated learning, ensuring accessibility and the reinforcement of Pancasila values. The expert validation results indicated that the product achieved an average score of 4.30 from content experts and 4.54 from media experts, both of which fall into the “very good” category. Furthermore, the practicality test results showed average scores of 4.39 from students and 4.75 from teachers, indicating that the interactive hybrid book is practical and effective as a learning medium for facilitating English reading activities in inclusive classrooms.